Constitutional PIGA mutations cause a novel subtype of hemochromatosis in patients with neurologic dysfunction - Muckenthaler, Lena; Marques, Oriana; Colucci, Silvia; Kunz, Joachim; Fabrowski, Piotr; Bast, Thomas; Altamura, Sandro; Höchsmann, Britta Elisabeth Hedwig; Schrezenmeier, Hubert; Langlotz, Monika; Richter-Pechańska, Paulina; Rausch, Tobias; et al. (Blood, 2022)
Glycosylphosphatidylinositol (GPI) anchors correctly localize 1% to 2% of human proteins to the cell membrane. Although biosynthesis of GPI anchors is commonly inactivated by somatic Phosphatidylinositol glycan anchor biosynthesis class A (PIGA) mutations in hematopoietic precursors in paroxysmal nocturnal hemoglobinuria (PNH), constitutional PIGA mutations are rare and have been implicated in severe impairment of neurologic development. Here we uncover that hypomorphic constitutional PIGA mutations cause a novel subtype of hereditary hemochromatosis (HH) by severely limiting GPI anchorage of hemojuvelin and ceruloplasmin.